Bifurcation analysis and multiplicity of steady states in a multistage agitated contactor for gas‐liquid processes. (4th September 2015) - Zhang, Lifeng; Pan, Qinmin; Rempel, Garry L.
<x xml:space="preserve">Abstract</x> In this work, a bifurcation analysis of steady states in a multistage agitated contactor (MAC) was conducted for typical gas‐liquid processes. A cascade of stirred tank reactors with a backflow was used to model the reactive flow in the MAC, and second‐order reaction kinetics was employed to represent typical gas‐liquid processes. In the developed model, the effect of temperature on gas solubility was taken into account. The multiplicity behaviour of steady states in such a reactor was investigated using a continuation method. Nonlinearity behaviours such as limit points and Hopf points were detected under various process parameters investigated in this work. A stability analysis was also conducted to determine whether the multiple steady state solutions observed were stable. The results suggested that a medium adiabatic temperature rise and small temperature difference are preferred to avoid system instability in operating such reactors.